ANALISA INSTRUMENTASI GEOTEKNIK UNTUK EVALUASI KEAMANAN BENDUNGAN URUGAN TANAH DI LODAN KABUPATEN REMBANG - deni setya aprianto; Ricky Eko Maulana; Indrastono Dwi Atmanto; Bambang Pardoyo (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2015)
Lodan dam is a dam made to stem Lodan River, located in the village Lodan, District Sarang, Rembang, Central Java. One way to determine the level of safety of dams is to use geotechnical instrumentation equipment consisting of water pressure instrumentation, deformation instrumentation and seepage instrumentation. This thesis discusses the pore water pressure were measured by means of piezometers. Monitor leaks and seepage using V-Notch Weir. And deformation using settlement survey point. From piezometer observation, it appears that the device responds to changes in water level only FP1, FP, FP3, PP6, PP10, PP13 and PP14 so that need for further treatment. For phreatic line drawing is still safe because the phreatic line does not cut the dam body. Seepage discharge is very small at less than 0.28 l / min / m, so it is still within safe limits. For vertical deformation observation is still safe because the SI value ≤ 0.02. In general, the security level Dam Lodan still within normal limits. Only the piezometers instruments that need further treatment.